Małżeńska wspólnota życia i miłości w świetle Ef 5,21-33 - Necel, Wojciech (Ius Matrimoniale)
As we face difficulties in defining marriage in accordance with the intention of the Creator, the author of marriage, St Paul’s letter to the Ephesians 5:21-23 brings the reader closer to an understanding of marriage as a communion of life and love which realizes its divine vocation in the sign of the spousal love of Christ toward His Church. An analysis of Paul's message to the Ephesians allows the author of this article to attempt an understanding of the theological aspects of marriage, pointing to the theological source of the rights and obligations in marriage and presenting marriage as a communion of spouses according to God’s will, mutually bestowing love, and being subject to each other.